Comparison of BFS and DFS Algorithm for Routes to Historical-Cultural Tourism Locations in Banten Province - Mochammad Darip; Sigit Auliana; Anam, Aan Khoirul; Parimin; Anugerah Agung (LPPM Telkom University Surabaya, 2024)
The development of information technology has had a significant impact in the tourism sector, especially in enriching the tourist experience, especially in the field of historical and cultural tourism. Banten Province, with its wealth of historical tourist attractions, is a major destination for tourists who want to explore and understand cultural and historical values in Indonesia. This research aims to maximize tourists' experience in visiting historical-cultural tourist attraction locations in Banten Province by choosing optimal travel routes, thereby increasing visit efficiency, minimizing travel time and distance, and enabling them to visit more locations in a limited time. In this research, the method used is research with a quantitative descriptive approach and graphic model design. The results of the simulation and testing of the graph model were analyzed on the selection of tourist travel routes using the Breadth-First Search (BFS) and Depth-First Search (DFS) algorithms based on graph models that describe the location of cultural-tourism objects. The simulation results show that BFS tends to produce travel routes that are more efficient in terms of distance traveled, while DFS optimizes the number of tourist site visits by exploring routes in depth. This research provides insight into these two approaches and their implications for travel decision making.